Data-Driven Fuzzy Weights-Of-Evidence Model for Identification of Potential Zeolite-Bearing Environments on Mars - (:unkn) unknown (My University, 2023)
The evolution of the climate and hydrochemistry of Mars is still a mystery but it must have been at least occasionally warm and wet to have formed the ancient fluvial and lacustrine landforms observed today. Terrestrial examples and geochemical modeling under proposed early Mars conditions show that zeolite minerals are likely to have formed under alkaline (pH > 8) conditions with low water/rock ratio and surface temperatures below 150°C. The identification and spatial association of zeolites on the surface of Mars could thus be used to reconstruct the paleoclimate, paleohydrochemistry, and geological evolution of some locations on Mars. Previous studies identified the zeolite analcime and discuss the difficulties of identifying other zeolite species on the surface of Mars using orbital spectroscopy. We used published global mineralogical, geological, geomorphological, hydrological, physical, and elemental abundance maps and the locations of hydrous minerals detected and mapped using orbital data to create a map that delineates favorable areas to look for zeolites on Mars. We used the data-driven fuzzy-based Weights-of-Evidence method to identify and map favorable areas for zeolites on the surface of Mars up to ±40° latitude toward the poles. The final map shows that the eastern and western Arabia deposits, some sites in the Medusae Fossae formation, and some areas within and near Valles Marineris, Mawrth Vallis, highlands north of Hellas, and the Terra Cimmeria and Terra Sirenum regions would be favorable areas to look for zeolites using targeted orbital spectral analysis or future in situ observations.
Keywords: Mars; zeolites; Weights-of-Evidence; fuzzy mapping; predictive modeling; ILWIS